2018
DOI: 10.3390/coatings8030114
|View full text |Cite
|
Sign up to set email alerts
|

The Properties of Binary and Ternary Ti Based Coatings Produced by Thermionic Vacuum Arc (TVA) Technology

Abstract: A series of the multicomponent thin films (binary: Ti-C; Ti-Ag and ternary: Ti-C-Ag; Ti-C-Al) were fabricated by Thermionic Vacuum Arc (TVA) technology in order to study the wear resistance and the anticorrosion properties. The effects of Ti amount on the microstructure, tribological and morphological properties were subsequently investigated. TVA is an original deposition method using a combination of anodic arc and electron gun systems for the growth of films. The samples were characterized using scanning el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Ternary coatings (TiNbC) exhibited the best corrosion and tribocorrosive performance along with low stress and high hardness compared to those of both binary coatings. This finding was accepted because ternary coatings have been found to be superior to binary ones [52]. The good corrosion resistance of TiNbC can be attributed to low crystalline size and the long paths over the grain boundaries delaying electrolyte penetration.…”
Section: Discussionmentioning
confidence: 95%
“…Ternary coatings (TiNbC) exhibited the best corrosion and tribocorrosive performance along with low stress and high hardness compared to those of both binary coatings. This finding was accepted because ternary coatings have been found to be superior to binary ones [52]. The good corrosion resistance of TiNbC can be attributed to low crystalline size and the long paths over the grain boundaries delaying electrolyte penetration.…”
Section: Discussionmentioning
confidence: 95%
“…The cathode acts as an electron gun heated by the intensity current of the filament and the anode is a carbon crucible, filled with a mixture of Co granules (99.95% metal basis), Ni granules (99.996%, metal basis), and aluminum granules (99.999%, metal basis) in a weight ratio of 1:1:1. The experimental setup for binary/ternary mixtures has been described elsewhere [ 32 , 33 , 34 ]. After ignition of the plasma, the power applied on the arc discharge was P = 375 W, where P = U a ·I a ; the symbols U a and I a represent the arc voltage and the arc current during deposition, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Other researchers developed black coatings of nickel on stainless steel substrate for solar thermal cells 6 . A previous study showed that when an element is "mixed" with other metals, advanced materials with amazing properties could be revealed and, from the economic point of view, the price of nal products would be decreased, which might be of particular advantage for industrial applications 7 . Consequently, researchers showed that when Ni mixed with Co at speci c percentage, the corrosion resistance and solar absorbance can be enhanced 8 9 .…”
Section: Introductionmentioning
confidence: 99%